Philippine forests and the Kyoto Protocol Opportunities and threats - Lasco, Rodel D. (Journal of Environmental Science and Management, 2000)
The paper examines the implications of the Kyoto Protocol specifically the Clean Development Mechanism (CDM), to Philippine tropical forests. The paper briefly summarizes the impacts of climate change to Philippine forests and their role in mitigating climate change. It analyzes the key issues in the landuse change and forestry (LUCF) sector relative to the CDM from the perspective of Philippine forestry. This is followed by a discussion of opportunities and threats arising out of the CDM. It is shown that there are many potential benefits that could come through CDM. However, without adequate guidelines, these benefits could be negated. The paper concludes with policy recommendations